Analisis Kurikulum 2013 pada Sekolah Dasar - Ina Magdalena; Aldi Sutisna; Rifdah Fauziah; Putri Indah Lestari (Jurnal Halaqah, 2020)
This research was conducted because the process of implementing the 2013 curriculum at SD Negeri Kp. Bulak III Pamulang has not been optimal, so learning is not optimal due to the lack of several technological tools that support the learning process in the 2013 curriculum. The purpose of this study is to determine the implementation process, and assessment. This research is a qualitative descriptive study. The subjects of this study were grade 1 - 6 teachers at SDN Kp. Bulak III Pamulang. While the object of his research is the implementation of the 2013 curriculum learning process in these elementary schools. Data collection techniques were obtained through observation and interviews. The data analysis technique uses the steps of reduction, presentation and conclusion drawing. The results showed that the implementation of the 2013 curriculum learning process in SDN Bp. Bulak III Pamulang, Pamulang Subdistrict, South Tangerang City was as follows: (1). Planning has gone according to the rules of the learning material. (2). The learning process in class is in accordance with the lesson plan, but there are still obstacles in time management and learning media. (3). Assessment has not gone well because the implementation has used thematic, but in its assessment the teacher must conduct an assessment per subject.